Driver Compensation: Impairment or Improvement?. (December 2015) - Young, Richard A.
Strayer et al.'s conclusion that their "cognitive distraction scale" for auditory-vocal tasks indicates "significant impairments to driving" is not supported by their data. Additional analysis demonstrates that slower brake reaction times during auditory-vocal tasks were fully compensated for by longer following distances to the lead car. Naturalistic driving data demonstrate that cellular conversation decreases crash risk, the opposite of the article's assumption. Hence, the scale's internal and external validities for indicating driving impairment are highly questionable.